The study on the effect of plasticizer on the properties of PVDF films - Chew, Gavin Weili. (2011)
A systematic study was carried out to investigate the effect of plasticizers on the properties of Polyvinylidene fluoride (PVDF) thin films. PVDF thin films of concentrations 5 wt% and 10 wt% were fabricated and it was observed that N, N Dimethylformamide (DMF) solution is able to completely dissolve a 5 wt% solution of PVDF after magnetic stirring for 24 hours but is unable to dissolve a 10 wt% solution. Ethylene Carbonate (EC) was added to the PVDF-DMF mixture as a plasticizer and was found to be effective in dissolving the PVDF powder. Characterization of the fabricated films with varying ratios of PVDF: EC was conducted and compared with respect to thermal, mechanical and surface properties.